2020
DOI: 10.3390/healthcare8010035
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Air Temperature Parameters and the Number of Deaths Stratified by Cause in Gifu Prefecture, Japan

Abstract: Objective: It is well known that air temperature is closely related to health outcomes. We investigated the relationship between air temperature parameters and the number of deaths stratified by cause in Gifu prefecture, Japan. Methods: The number of deaths stratified by cause in Gifu prefecture Japan between January 2007 and December 2016 was obtained from the official homepage of Gifu prefecture, Japan. Air temperature parameters (°C), i.e., the mean air temperature, mean of the highest air temperature, mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…Consistent with this finding, we previously reported that the number of deaths due to renal failure was closely associated with air temperature parameters and was significantly higher in January than in other months in Gifu prefecture, which is centrally located in Japan [13]. However, the relationship between the number of deaths due to renal failure and air temperature parameters in other areas and throughout Japan remains unclear.…”
Section: Introductionsupporting
confidence: 69%
“…Consistent with this finding, we previously reported that the number of deaths due to renal failure was closely associated with air temperature parameters and was significantly higher in January than in other months in Gifu prefecture, which is centrally located in Japan [13]. However, the relationship between the number of deaths due to renal failure and air temperature parameters in other areas and throughout Japan remains unclear.…”
Section: Introductionsupporting
confidence: 69%
“…A trend analysis of the number of deaths due to senility was conducted by the Jointpoint regression program, 4.8.0.1 (National Cancer Institute) [ 16 , 17 ]. To compare variations in the number of deaths due to senility with other major causes of death in Japan, we calculated the coefficient of variation (CV: standard deviation/mean) of 5 major causes of death each year between 1995 and 2018 in Japan, and compared CV (among 47 prefectures for 24 years) using the Kruskal-Wallis test and Steel test [ 18 ]. We also examined the relationship between the number of deaths due to senility and socioeconomic factors in Japan using simple and multiple regression analyses, where p < 0.05 was significant.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, weather, or meteorological factors are related to ambulance dispatches, the number of deaths, and traumas. [2][3][4] Also, the total numbers of deaths have a relationship with air temperatures, [5][6][7][8] and winter also relates to trauma like fractures 9 and motor vehicle accidents. 10 However, there are 4 seasons in Japan with meteorological flections.…”
Section: Introductionmentioning
confidence: 99%